KERJASAMA ORANGTUA DAN GURU MENDORONG KEGIATAN BELAJAR UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA - SARIAMAN GULTOM (JURNAL ILMIAH SIMANTEK, 2019)
Learning achievement is very important in the process of improving the quality of education today. Given the declining quality of education in Indonesia today, the role of parent and teacher collaboration is very important in supporting the improvement of student learning achievement.